Deficiency of Mettl3 in Bladder Cancer Stem Cells Inhibits Bladder Cancer Progression and Angiogenesis - Wang, Ganping; Dai, Yarong; Li, Kang; Cheng, Maosheng; Xiong, Gan; Wang, Xiaochen; Chen, Shuang; Chen, Zhi; Chen, Jianwen; Xu, Xiuyun; Ling, Rong-song; Peng, Liang; et al. (Frontiers in Cell and Developmental Biology, 2021)
RNA N6-methyladenosine is a key step of post-transcriptional modulation which involves in governing gene expression. The m6A modification catalyzed by Mettl3 has been widely recognized as a critical epigenetic regulation process for tumorigenic properties in various cancer cell lines, including bladder cancer. However, the in vivo function of Mettl3 in bladder cancer remains largely unknown. In our study, we found that ablation of Mettl3 in bladder urothelial attenuates the oncogenesis and tumor angiogenesis of bladder cancer using transgenic mouse model. In addition, conditional knockout of Mettl3 in K14+ bladder cancer stem cell population leads to inhibition of bladder cancer progression. Coupled the global transcriptome sequencing and methylated RNA immunoprecipitation sequencing results, we showed that deletion of Mettl3 leads to the suppression of TEK and VEGF-A through reduced abundance of m6A peaks on specific region. In addition, depletion of Mettl3 result in decrease of both mRNA and protein levels of TEK and VEGF-A in vitro. Taken together, Mettl3-mediated m6A modification is required for the activation of TEK-VEGF-A-mediated tumor progression and angiogenesis. Our findings may provide theoretical basis for bladder cancer treatment targeting Mettl3.